Extracellular Vesicles Released From Articular Chondrocytes Play a Major Role in Cell–Cell Communication. Issue 4 (27th November 2019) - Liu, Xiaoming; Shortt, Claire; Zhang, Fenglin; Bater, Mariah Q.; Cowman, Mary K.; Kirsch, Thorsten
ABSTRACT: The purpose of this investigation was to determine the role of extracellular vesicles (EVs), released from articular chondrocytes in a physiological or pathological state, in cell–cell communication with other articular chondrocytes or chondrocyte precursor cells. The conditioned medium from interleukin‐1β (IL‐1β)‐treated human articular chondrocytes stimulated catabolic events and inhibited type II collagen expression in articular chondrocytes to a much greater degree than medium from IL‐1β‐treated chondrocytes after complete removal of EVs. The vehicle‐treated and IL‐1β‐treated human articular chondrocytes released EVs of similar size; however, the number of EVs released by IL‐1β‐treated chondrocytes was markedly higher than the number of EVs released from the vehicle‐treated cells. Furthermore, our findings demonstrate that similar to medium from IL‐1β‐treated chondrocytes containing EVs, EVs isolated from medium of IL‐1β‐treated chondrocytes stimulated catabolic events in articular chondrocytes, whereas EVs isolated from the medium of vehicle‐treated chondrocytes inhibited catabolic events and increased messenger RNA levels of aggrecan and type II collagen in IL‐1β‐treated chondrocytes. Furthermore, the medium containing EVs from vehicle‐treated articular chondrocytes or EVs isolated from this medium stimulated chondrogenesis of C3H10T1/2 cells, whereas medium containing EVs from IL‐1β‐treated chondrocytes or EVs isolated from this medium inhibited chondrogenesis. Our findings suggest that EVs released by articular chondrocytes play a key role in the communication between joint cells and ultimately in joint homeostasis, maintenance, pathology, and repair. © 2019 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 38:731‐739, 2020